OPTIMALISASI PERLINDUNGAN KONSUMEN PANGAN INDUSTRI RUMAH TANGGA MELALUI PENGUATAN SISTEM KEAMANAN PANGAN TERPADU - Bambang Hermanu; Dyah Ilminingtyas Wahyu Handayani (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2019)
This study further examines the previous research that has formulated an integrated food safety system development model in realizing the optimal implementation of PIRT product distribution licenses. With the socio-legal research approach method, it does not only examine normative matters, but also data collection in the field through comprehensive observation and interviews with related parties and is analyzed qualitatively. What is more emphasized from the results of this study is focused on aspects of the embodiment of consumer food consumer protection in the home industry through strengthening synergistic and integrated food security systems. BasedonLawNumber18Year2012concerningfood,alegalchannelis opened for consumers to claim compensation when they suffer losses due to consuming food that causes harm to it, along with the circulation of food that does not meet health requirements namely, safe, quality, and nutritious so that can cause harm to consumers.